IMPROVING THE QUALITY OF EDUCATION UNDER THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN HIGHER EDUCATION INSTITUTIONS OF THE REPUBLIC OF UZBEKISTAN - Lee Dmitry Eduardovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the modernization of the content of modern education on the basis of advanced foreign experience, the formation of an innovative educational environment based on information and communication technologies.